Rokat Tase’ in Review of Maqashid Syariah Perspective of Muhammad Thahir Ibnu Asyur: Case Study of Madura Island - Moh. Hamzah (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
Local wisdom embedded in a community group, of course, will become an inseparable part of life, one of which is the rokat tase’ tradition which is routinely carried out by several coastal communities. Therefore, this article will examine and analyze in depth the rokat tase' tradition with maqashid sharia from Imam Muhammad Thahir Ibn Ashur. This article, which is essentially an empirical legal research, will comprehensively use the maqashid sharia approach and qualitative descriptive methods. The result of this research is that in the first concept in his thought, Ibn Ashur distinguishes maqāṣid ash-syarīʻah into maqāṣid ash-syarah al-ʻāmah and maqāṣid ash-syarīʻah al-khāṣṣah bianwāʻ al-muʻāmalāt. Furthermore, he describes the rationale in determining maqasid, namely with fitrah, maslahah, and ta'lil. Finally, he explains the operationalization of maqasid theory in three ways, namely through al Maqam, Istiqra' and distinguishing between wasail and maqasid. In addition, after being studied in depth and competently through maqashid sharia with Ibn Asyur's thoughts on the implementation of the rokat tase' tradition in Madura in particular, presumably in this tradition it contains values that are quite large. Among other things are the achievement of the problems of the people through the establishment of Islam in the tradition, the realization of good social benefits among others, the maintenance of the welfare of the community in avoiding future dangers and the realization of the economic development of the people through the implementation of the existing rokat tase' tradition. Thus, for the considerable benefit in it, this tradition deserves to be maintained and preserved properly and correctly. Kearifan lokal yang tertanam di dalam suatu kelompok masyarakat, tentunya akan menjadi bagian hidup yang tidak dapat terpisahkan. Salah satunya seperti tradisi rokat tase’ yang rutin dilaksanakan oleh beberapa masyarakat di pesisir pantai. Oleh karena itu, artikel ini akan mengkaji dan menganalisis secara mendalam tradisi rokat tase’ dengan maqashid syariah dari Imam Muhammad Thahir Ibnu Ashur. Artikel yang pada esensinya merupakan penelitian hukum empiris ini, secara komprehensif akan menggunakan pendekatan maqashid syariah dan metode deskriptif kualitatif. Hasil dari penelitian ini adalah pada konsep pertama dalam pemikirannya, Ibnu Ashur membedakan maqāṣid asy-syarīʻah menjadi maqāṣid asysyarīʻah al-ʻāmah dan maqāṣid asy-syarīʻah al-khāṣṣah bianwāʻ al-muʻāmalāt. Selanjutnya ia menguraikan dasar pemikiran dalam menetapkan maqasid yaitu dengan fitrah, maslahah, dan ta’lil. Terakhir ia menjelaskan operasionalisasi teori maqasid dengan tiga cara yaitu melalui al Maqam, Istiqra’ serta membedakan antara wasail dan maqasid. Selain itu, setelah dikaji secara mendalam dan kompeten melaui maqashid syariah dengan pemikirannya Ibnu Asyur terhadap pelaksanaan tradisi rokat tase’ di Madura khususnya, kiranya dalam tradisi tersebut mengandung nilai-nilai kemaslahatan yang cukup besar. Antara lain adalah tercapainya kemaslahatan umat melalui tegaknya agama Islam dalam tradisi tersebut, terwujudnya kemaslahatan sosial yang baik antar sesama, terjaganya kesejahteraan masyarakat dalam menghindari bahaya yang akan datang dan terealisasikannya pembangunan ekonomi umat melalui pelaksanaan tradisi rokat tase’ yang ada. Dengan demikian, atas kemaslahatan yang cukup besar di dalamnya, tradisi ini patut untuk dipertahankan dan dilestarikan dengan baik dan benar.